2018
DOI: 10.1523/jneurosci.3818-16.2018
|View full text |Cite
|
Sign up to set email alerts
|

α2δ-4 Is Required for the Molecular and Structural Organization of Rod and Cone Photoreceptor Synapses

Abstract: αδ-4 is an auxiliary subunit of voltage-gated Ca1.4 L-type channels that regulate the development and mature exocytotic function of the photoreceptor ribbon synapse. In humans, mutations in the gene encoding αδ-4 cause heterogeneous forms of vision impairment in humans, the underlying pathogenic mechanisms of which remain unclear. To investigate the retinal function of αδ-4, we used genome editing to generate an αδ-4 knock-out (αδ-4 KO) mouse. In male and female αδ-4 KO mice, rod spherules lack ribbons and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(107 citation statements)
references
References 49 publications
4
88
0
Order By: Relevance
“…In this study we identified two zebrafish orthologs of human CACNA2D4, harboring the canonical protein domain compo-sition typical of all a 2 d family members, indicative of functional conservation. We found that Cacna2d4b is essential for synaptic expression of Cacna1fa in photoreceptors of larval zebrafish, comparable to mouse Cacna2d4 23,24 and other a 2 d subunits. [51][52][53] In zebrafish, the two paralogs show partial subfunctionalization: cacna2d4a-KO did not affect Cacna1fa expression, which is consistent with its more prominent expression in the INL.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…In this study we identified two zebrafish orthologs of human CACNA2D4, harboring the canonical protein domain compo-sition typical of all a 2 d family members, indicative of functional conservation. We found that Cacna2d4b is essential for synaptic expression of Cacna1fa in photoreceptors of larval zebrafish, comparable to mouse Cacna2d4 23,24 and other a 2 d subunits. [51][52][53] In zebrafish, the two paralogs show partial subfunctionalization: cacna2d4a-KO did not affect Cacna1fa expression, which is consistent with its more prominent expression in the INL.…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, even though we found the cone ERG responses to be significantly impaired, the amplitude of the b-wave was only slightly reduced, which is in accordance with the rather mild ERG defect in patients, 7,22,46 but in contrast to the more severe phenotype in cacna2d4-KO mice. 6,23,24 Furthermore, we were surprised to find that loss of Cacna2d4a and b together with the substantial reduction in Cacna1fa levels did not elicit a stronger effect on ERG response as well as on ribbon synapse structure and general retinal morphology in double-KO. This is particularly surprising in light of the strong defects in cacna1fa-KO zebrafish and the fact that not only Cacna1fa was proven important for ribbon synapse development and maintenance in zebrafish, 20 but also Cacna2d4 was shown to have a similar function in murine rod photoreceptors.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations